Robust Coordination Scheme for Microgrids Protection Based on the Rate of Change of Voltage - Mohamed Ahmed Dawoud (IEEE, 2021)
The wide application of microgrid concept leads to challenges for the traditional protection of distribution networks because of the changes in short circuit level and network topology during the two modes of microgrid operation. This paper proposes a promising solution for these problems by offering a new protection coordination scheme not affected by the variation of short circuit level or the changes in network topology. The proposed protection scheme is based on local measurements at relay location with low sampling frequency by computing the rate of change of fundamental voltage (ROCOV) to detect different fault types, identify the faulty zone accurately and guarantee robust coordination between primary and backup relays. The proposed coordination scheme can be achieved by optimizing either two settings for relay characteristic (time dial setting and pickup value) or four settings (time dial setting, pickup and the parameters that control the characteristic shape A & $B$ )). The proposed scheme is extensively tested using MATLAB simulations on the modified IEEE 14 bus meshed network embedded with synchronous/inverter-based distributed generation units under wide variations in operating conditions and short circuit levels for both grid-connected and islanded modes of operation. The achieved results confirm that the proposed coordination scheme can maintain the coordination between primary and backup relays for different fault locations, types and different topologies. It provides selective, reliable, and secured microgrid operation compared with conventional schemes, using fault current limiters and some other techniques discussed in the literature.